The Nuclear Factor Kappa B (NF-kB) signaling in cancer development and immune diseases - Zinatizadeh, Mohammad Reza (Genes Dis, 2020)
The nuclear factor kappa B (NF-kB) family of transcription factors plays an essential role as stressors in the cellular environment, and controls the expression of important regulatory genes such as immunity, inflammation, death, and cell proliferation. NF-kB protein is located in the cytoplasm, and can be activated by various cellular stimuli. There are two pathways for NF-kB activation, as the canonical and non-canonical pathways, which require complex molecular interactions with adapter proteins and phosphorylation and ubiquitinase enzymes. Accordingly, this increases NF-kB translocation in the nucleus and regulates gene expression. In this study, the concepts that emerge in different cellular systems allow the design of NF-kB function in humans. This would not only allow the development for rare diseases associated with NF-kB, but would also be used as a source of useful information to eliminate widespread consequences such as cancer or inflammatory/immune diseases.